PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR FORMAL SISWA PADA PEMBELAJARAN IPA DIKELAS VIII MTs N 1 ROKAN HULU FILIAL TAMBUSAI UTARA - Wahyuni, Erna; Zulhelmi, Zulhelmi; Ma’aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the increase of formal thinking ability in science lesson by applying cooperative learning model of think talk write type. This research was conducted in MTs N 1 Rokan Hulu Filial North Tambusai in January to May 2018. The population in this study is the students of class VIII 2nd semester of the academic year 2017/2018 consisting of 3 classes. While the sample in this research is 2 homogenous class which chosen at random. The design of this research is Quasi Experimental in the form of Nonequivalent Control Group Design. The instrument of data collection in this research is a formal thinking skill test consisting of 10 items of multiple choice by using descriptive analysis and inferential analysis. From the descriptive analysis, the result of absorption ability of the average of the experimental class students before the treatment is 30,32% with the less good category, after given the students absorbance treatment equal to 60,32% with good enough category while the absorption average of control class before treatment by 37.50% in the less favorable category, after being subjected to average absorption treatment increased by 50% with good enough category. The formal thinking ability of the experimental class students has moderate category with N-Gain 0,48 while control class is 0.22 with low category. Based on inferential analysis through independent sample t test obtained Sig value. (2-tailed) = 0.037 <0.05 which means there is a significant difference. The result of this research can be concluded that the use of cooperative type model of think talk write can improve students' formal thinking ability in MTs N 1 Rokan Hulu Filial Tambusai Utara on the material of geteran, wave and sound.Key Words: Formal Thinking Ability, Cooperative Model, and Think Talk Write